Examples with solutions for Negative Exponents: Presenting powers with negative exponents as fractions

Exercise #1

Insert the corresponding expression:

(120)7= \left(\frac{1}{20}\right)^{-7}=

Video Solution

Step-by-Step Solution

To simplify the expression (120)7 \left(\frac{1}{20}\right)^{-7} , we will apply the rule for negative exponents. The key idea is that a negative exponent indicates taking the reciprocal and converting the exponent to a positive:

  • Start with the expression: (120)7 \left(\frac{1}{20}\right)^{-7} .
  • Apply the negative exponent rule: (1a)n=an \left(\frac{1}{a}\right)^{-n} = a^n .
  • For our expression: (120)7 \left(\frac{1}{20}\right)^{-7} becomes 207 20^7 .

Therefore, (120)7 \left(\frac{1}{20}\right)^{-7} simplifies to 207 20^7 .

Thus, the correct answer is 207 20^7 .

Answer

207 20^7

Exercise #2

Insert the corresponding expression:

(160)4= \left(\frac{1}{60}\right)^{-4}=

Video Solution

Step-by-Step Solution

To solve for (160)4 \left(\frac{1}{60}\right)^{-4} , we apply the rule for negative exponents.

Step 1: Use the negative exponent rule: For any non-zero number a a , an=1an a^{-n} = \frac{1}{a^n} . Thus,

(160)4=(601)4 \left(\frac{1}{60}\right)^{-4} = \left(\frac{60}{1}\right)^4 .

Step 2: Simplify (601)4\left(\frac{60}{1}\right)^4 by recognizing the identity 601=60\frac{60}{1} = 60, so it follows that:

(601)4=604 \left(\frac{60}{1}\right)^4 = 60^4 .

Therefore, the simplified expression is 604 60^4 .

The correct answer is 604 60^4

Answer

604 60^4

Exercise #3

Insert the corresponding expression:

(13)4= \left(\frac{1}{3}\right)^{-4}=

Video Solution

Step-by-Step Solution

To solve this problem, we'll follow these steps:

  • Step 1: Identify the given expression with a negative exponent.
  • Step 2: Apply the rule for negative exponents, which allows us to convert the expression into a positive exponent form.
  • Step 3: Perform the calculation of the new expression.

Now, let's work through each step:

Step 1: The expression given is (13)4 \left(\frac{1}{3}\right)^{-4} , which involves a negative exponent.

Step 2: According to the exponent rule (ab)n=(ba)n \left(\frac{a}{b}\right)^{-n} = \left(\frac{b}{a}\right)^n , we can rewrite the expression with a positive exponent by inverting the fraction:

(13)4=(31)4=34 \left(\frac{1}{3}\right)^{-4} = \left(\frac{3}{1}\right)^4 = 3^4 .

Step 3: Calculate 34 3^4 .

The calculation 34 3^4 is as follows:

34=3×3×3×3=81 3^4 = 3 \times 3 \times 3 \times 3 = 81 .

However, since the problem specifically asks for the corresponding expression before calculation to numerical form, the answer remains 34 3^4 .

Therefore, the answer to the problem, in terms of an equivalent expression, is 34 3^4 .

Answer

34 3^4